Revenue decentralization, central oversight and the political budget cycle: Evidence from Israel - Thushyanthan Baskaran; Sebastian Blesse; Adi Brender; Yaniv Reingewertz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
This paper examines whether revenue decentralization and direct external financial supervision affect the incidence and strength of political budget cycles, using a panel of Israeli municipalities during the period 1999-2009. We find that high dependence on central government transfers - as reflected in a low share of locally raised revenues in the municipalitys budget - exacerbates political budget cycles, while tight monitoring - exercised through central government appointment of external accountants to debt accumulating municipalities - eliminates them. These results suggest that political budget cycles can result from fiscal institutions that create soft budget constraints: that is, where incumbents and rational voters can expect that the costs of pre-election expansions will be partly covered later by the central government.
Keywords: D72; H72; H74; E62; 330; political budget cycles; soft budget constraint; local governments; decentralization